PENGGUNAAN MEDIA LAGU POP DALAM PEMBELAJARAN MENULIS CERPEN REALIS SISWA KELAS IX A SMP NEGERI 9 KOTA JAMBI TAHUN PELAJARAN 2016/2017 - R. Bintang Jaya Setia; Erlina Zahar; Ade Rahima (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to describe students ability in writing realist short story at students class IX A SMP Negeri 9 Kota Jambi Academic Year 2016/2017. The type of this research is qualitative descriptive. The data of this research is primary and secondary data. The primary data is taken directly, from students exercise in writing realist short story while secondary data is taken from some sources in Batanghari University library and province library. The data is collected by using observation, interview, exercise, and documentation. From the analysis, it shows that there are 5 students fall into very good criteria (interval up to 80), there are 21 students fall into good criteria (interval 70-79), there are 11 students fall into fair criteria (interval 60-69),and there is 1 student falls into below average (interval up to 59). So, it can be concluded that students ability in wiritng realist short story fall into good criteria with interval 70.Kata Kunci:pop song, realist short story, students